Regional heterogeneity of cerebral blood flow response to graded pressure-controlled hemorrhage - Waschke, Klaus F.; Riedel, Martin; Lenz, Christian; Albrecht, Detlef M.; Ackern, Klaus van; Kuschinsky, Wolfgang (The journal of trauma, 2004)
Background - Little is known about the regional distribution of cerebral blood flow (CBF) in nonanesthetized animals during periods of lowered blood pressure. The present investigation addresses the specific reaction patterns of local cerebral blood flow (LCBF) in comparison with mean CBF during graded pressure-controlled hemorrhagic shock in conscious rats. - Methods - Conscious rats were subjected to graded pressure-controlled hemorrhage (to 85, 70, 55, or 40 mm Hg) by arterial blood withdrawal. After a period of 30 minutes, blood pressure was stabilized by withdrawal or reinfusion of blood. LCBF was determined autoradiographically by the iodo(14C)antipyrine method in 34 brain structures, and mean CBF was calculated and compared with the values of nonhemorrhaged control animals. - Results - Mean CBF remained unchanged except for the group with the lowest blood pressure of 40 mm Hg (decrease in CBF of 28%). Otherwise, LCBF was increased in some brain structures at an unchanged mean CBF. Congruently, at 40 mm Hg, the decrease in mean CBF did not show up in all brain structures, the local pattern of CBF varying between an unchanged and a profoundly decreased CBF. The mean coefficient of variation of CBF was increased with the severity of hemorrhagic shock, which indicates an enhanced heterogeneity of CBF. - Conclusion - Because of the substantial heterogeneity in the responses of LCBF to pressure-controlled hemorrhage, autoregulation of CBF during pressure-controlled hemorrhagic shock has to be reconsidered on a regional basis.